Theoretical conceptualization of insurance protection - Shupa, Lesia (Skhid, 2015)
The aim of the research is the systematization of theoretical and applied approaches to understand the essence of insurance protection and development of new approaches of the theoretical conceptualization of social economic category in the current economic conditions. Theoretical and applied approaches of defining the essence of insurance protection are investigated, as well as the advantages and disadvantages of each of them are showed. It is proved that the essence of insurance protection is more fully showed in its wide sense it as a complex social category. Basic features inherent in this economic category are systemized, which distinguish it among other related categories and concepts. The sources and fund structure of insurance protection - natural and cash reserves are analyzed in ditail, which are strictly purposeful that is warning, damages for adverse events (risks) caused by adverse events (risks), and participants of their formation, distribution and usage are identified. It is stated that the insurance protection is the social economic category, which covers a number of economic relations in the commercial and social insurance, self-insurance and mutual insurance that have a significant difference in subject, object and subjects of insurance relations, sources and forms of insurance protection. A refined definition of the economic category of insurance protection as an integrated social category is proposed which encompasses the totality of economic relations arising between the parties of certain purpose fund organization, created by natural and financial resources to be used to prevent, reduce or overcome the negative impact of adverse events (risks) and compensation of their effects in the process and uninterrupted social production, ensuring the economic growth and financial stability in the country, raising the material welfare and their social security.